Oral Health Literacy and COVID-19 Pandemic Anxiety and Concerns Among Iranian Orthodontic Patients - Mahdjoube Goldani Moghadam; Maryam Omidkhoda; Hanieh Kazemi (Galenos Yayinevi, 2021)
Objective: This study aims to evaluate the impact of the COVID-19 pandemic on orthodontic appointments, and the concerns and anxiety levels of orthodontic patients in Iran.Methods: An anonymous 40-question questionnaire was sent online to the patients of private orthodontic clinics in 2 cities of Birjand, and Mashhad, capitals of Eastern provinces of Iran. Orthodontic patients of Mashhad dental school received the questionnaire as well. Descriptive statistics were reported, and the association between gender, oral health literacy (OHL), and adherence to orthodontic appointments and attendance, along with data on feeling, concern, and level of anxiety regarding quarantine/coronavirus pandemic were evaluated using the chi-square analysis.Results: Three hundred twenty-four patients, with a mean age of 32.43 years, answered the questionnaire. Fifty-seven percent of participants said that they only left home for their daily requirements. Seventy-two percent of the participants reported feeling calm about the COVID-19 pandemic and its consequences. Most of the patients (74%) said that they would attend their orthodontic appointment in case of urgency, and 41% of patients declared that their greatest concern was the probability of a delay in completion of treatment. Forty-five percent of patients had adequate OHL. There was a significant association between OHL and willingness to attend orthodontic treatment, concerns regarding the impact of the pandemic on orthodontic treatment, and the frequency of daily teeth brushing.Conclusion: Women respected the quarantine more than men. Patients with higher OHL were more willing to attend their appointments, but only in case of an emergency, due to the outbreak of COVID-19. Women were more concerned and had better oral hygiene behaviors.